2017
DOI: 10.1016/j.cpr.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Interventions that target improvements in mental health for parents of children with autism spectrum disorders: A narrative review

Abstract: • Narrative review of mental health interventions for parents of autistic children • Some treatments reported improvements in stress, depression, and anxiety.• Post-test produced weaker effects than follow-up assessments two months and beyond.• Small sample size, homogeneity, and self-report limited generalizability of results • Outcomes encouraging, but existing data cannot yet support definitive conclusions a b s t r a c t a r t i c l e i n f o Prevalence of autism spectrum disorders (ASD) suggest that one i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(67 citation statements)
references
References 73 publications
2
54
0
Order By: Relevance
“…Respite care and most interventions studied so far do not appear to have consistent effects on reducing psychological stress or depression (Dababnah & Parish, 2016; Whitmore, 2016). Social support groups are natural and accessible interventions for caregivers, and can be helpful for some (Da Paz & Wallander, 2017). However, depending on types of groups, especially those not guided by a professional, there could be modeling or norms for non-acceptance and despair.…”
Section: Discussionmentioning
confidence: 99%
“…Respite care and most interventions studied so far do not appear to have consistent effects on reducing psychological stress or depression (Dababnah & Parish, 2016; Whitmore, 2016). Social support groups are natural and accessible interventions for caregivers, and can be helpful for some (Da Paz & Wallander, 2017). However, depending on types of groups, especially those not guided by a professional, there could be modeling or norms for non-acceptance and despair.…”
Section: Discussionmentioning
confidence: 99%
“…However, a growing number of studies have targeted parent-focused outcomes such as maternal depression and stress management with methods ranging from mindfulness interventions and parent-clinician partnerships to relaxation training and manual-based stress reduction practices (Da Paz & Wallander, 2017). The current research joins this emerging trend by directly targeting improvement in parent outcomes, rather than relying on indirect collateral effects of child-focused treatment.…”
Section: Treatment To Benefit Parents Directlymentioning
confidence: 94%
“…Studies obtained from searches conducted in the electronic databases as well as identified from the references were complied, and their citations were exported to EndNote X8 (Clarivate Analytics, 2019). Duplicate studies were removed electronically using EndNote X8.…”
Section: Search Methodsmentioning
confidence: 99%
“…However, the two reviews were outdated as they were conducted more than a decade ago. Da Paz and Wallander () narratively reviewed varied forms of psychological interventions on their efficacy in augmenting the mental health of parents with children living with ASD, but inconclusive evidence was found. Four reviews examined the efficacy of mindfulness‐based interventions on the mental health of parents of children with developmental disabilities (Cachia et al, ; Keenan‐Mount et al, ; Ó Donnchadha, ; Rayan & Ahmad, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation